Uwarunkowania działalności banków spółdzielczych w Polsce determinowane tendencjami rynkowymi - Zaleska, Małgorzata (Conditions of operations of co-operative banks determined by market tendencies, 2006)
Taking into consideration the significance of co-operative bank sector in some environments and their big number and also the fact that Polish banking supervisory authorities have full influence over this market segment, the operations of co-operative banks in Poland were analyzed against the market tendencies. Purpose of this study: Characterization of the directions of changes on the financial market, with the particular interest on the banking market; Indication of the different conditions of co-operative banks’ operations in terms of their size and place of operations; Analysis of the selected financial ratios in the biggest and smallest co-operative banks, with the particular interest on the quality of receivables and profitability of assets; Evaluation of the core areas of the co-operative banks’ operations, this is credit activities and acquisition of sources of financing (deposits), Upon carrying out the analysis the following conclusions have been formulated: Co-operative banks’ sector is not a homogenous group, they are further diversified in terms of size and place of operations and for this reason the development strategies of co-operative banks shall be differentiated; Big co-operative banks are characterized by poorer quality of receivables and lower profitability than smaller co-operative banks; in the co-operative banks’ sector the quality of receivables is low resulting from financial intermediation, i.e. the co-operation with this market segment is quite of a challenge for co operative banks; the key customer of co-operative banks is a farmer and these banks may face a problem if other players on the financial market will intensify their efforts to take over this group of customers; there is a need for rebuilding the age structure of banks’ deposit holders, since the gross majority of them are elderly people.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1128, s. 101-108